Tajdid Fiqh Mazhab Syafi’i di Malaysia - Ali, Abdul Karim (Jurnal Fiqh, 2007)
The madhahib of fiqh had been through of various processes; establishment, strengthening, development, diffusion and reform. As far as Shafi’ite madhhab is concerned, it has been through all those processes. The reform and tajdid in the Shafi`ite madhhab can be evaluated in term of its establishment, i.e. proper selection of methods and approaches between two schools of thought; Hijaz and Iraq, between two madhahib of Imam Abu Hanifah and Imam Malik. It also can be seen through his two doctrines; qadim and jadid. As far as Malaysia is concerned, Islam in Malaysia has been spread and taught in accordance to Shafi’ite madhhab. It has been strengthened by education system, legal and others. Right now, if there is a difficult and complicated issue, those interested parties have several options, whether to refer to aqwal in Shafi’ite madhhab even though it could be weak, or to opt views of other madhhab that could drive the maslahat to the public. In other word, it could lead to the issues of talfiq, taqlid and takhayyur. Therefore, this article attempts to elucidate issues of fiqh in Shafi’ite madhhab can grow and solve in Malaysia without to jump to other madhhab. In other word how to develop those issues in the framework of Imam Shafi’ite.